Chromium-Modified Ultrathin CoFe LDH as High-Efficiency Electrode for Hydrogen Evolution Reaction - Jun-Jun Zhang; Meng-Yang Li; Xiang Li; Wei-Wei Bao; Chang-Qing Jin; Xiao-Hua Feng; Ge Liu; Chun-Ming Yang; Nan-Nan Zhang (Nanomaterials, 2022)
Hydrogen evolution reaction (HER) has a dominant function in energy conversion and storage because it supplies a most effective way for converting electricity into sustainable high-purity hydrogen. Layered double hydroxides (LDHs) have shown promising performance in the process of electrochemical water oxidation (a half-reaction for water splitting). Nevertheless, HER properties have not been well released due to the structural characteristics of related materials. Herein, a simple and scalable tactics is developed to synthesize chromium-doped CoFe LDH (CoFeCr LDH). Thanks to oxygen vacancy, optimized electronic structure and interconnected array hierarchical structure, our developed ternary CoFeCr-based layered double hydroxide catalysts can provide 10 mA cm−2 current density at −0.201 V vs. RHE with superior long-term stability in alkaline electrolyte. We anticipate that the simple but feasible polymetallic electronic modulation strategy can strengthen the electrocatalytic property of the layered double hydroxides established in the present study, based on a carbon neutral and hydrogen economy.